SYNERGISTIC ANTI-DIABETIC EFFECTS OF COMBINED ETHANOLIC PLANT EXTRACTS, Verbascum thapsus, Trigonella foenum graecum, Ficus semicordata AND Cocos nucifera (VTFC), IN STREPTOZOTOCIN INDUCED DIABETIC RATS: A POLYHERBAL COMBINATION (Journal of Pharmaceutical Negative Results, 2023)
Objective: To evaluate synergistic antidiabetic effects of combination of ethanolic plant extracts, Vervascum thapsus (Leaves), Trigonella foenum graecum( Seeds), Ficus semicordata (leaves) and cocos nucifera (Husk) in streptozotocin induced diabetic rats Verbascum thapsus (Mullein), Trigonella foenum graecum (Fenugreek or Methi), Ficus semicordata (Drooping fig) andcocos nucifera (Nariyal) are traditionally used in the treatment of various disease including diabetes mellitus. The anti-diabetic activity of each individual plant species is well documented, but their combined or synergistic effect is unknown, so currentinterest is to enhance therapeutic action and reduce the concentration of single herb, thereby decreasing adverse effects. Current study is evaluated the hypoglycaemic activity of the combined mixture of ethanol extract of Leaves of Vebascum thapsus, Seeds of Trigonella foenum graecum, leaves of Ficus semicordata and husk of coconut (VTFC) at different doses in streptozotocin induced diabetic rats. Diabetic rats were treated with combined ethanolic extracts of VTFC at doses 810 mg for 300 g rat (112.50 mg AEVT, 600 mg AETFG, 22.50 mg AECNH, 75 mg AEFS) calculated by design-expert software by using Box Behnken design per day or glibenclamide 5 mg/body weight for 7 days. VTFC extracts significantly lowered elevated fasting blood glucose level. The results were nearly equipotent with glibenclamide, so it is suggested that in addition to its hypoglycaemic activity VTFC protects liver, kidney blood, pancreas against diabetic injury. This is the first synergistic study of selected plant species to evaluate possible role for this mixture in treatment of diabetes.